The effect of paint coatings on detection of vertical surface cracks in metals by induction thermography. (June 2019) - Wang, Yongheng; Gao, Xiaorong; Finckbohner, Michael; Netzelmann, Udo
Abstract: The effect of polymer coatings on the detection of surface cracks by induction thermography was investigated. Paint applied in defined thickness, layers of black adhesive tape and of sellotape and thicknesses of 0.05–0.5 mm were studied. Artificial vertical cracks in ferritic steel and natural cracks in a forged ferritic steel part were investigated. An analytical thermal wave model was set up. Experiments performed at 25 kHz induction frequency with pulses of 0.2s duration showed decrease of absolute and relative contrasts of the crack signals with increasing coating thickness. The effect of infrared transparency of coatings was visible in the experiments and treated in an analytical model of the radiation from the sample. Highlights: Induction thermography under polymer coatings is possible. Investigations as a function of the coating thickness. Effect of partial infrared transparence of coating is decribed and analytically and experimentally studied. Investigation on natural coated cracks.